Penerapan program galeri investasi bursa efek indonesia dalam menunjang kemandirian mahasiswa - Mahendra, Prasetya Tri; Novaliana, Ika (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
This study aims to analyze the Indonesia Stock Exchange Investment Gallery program in supporting student independence his study uses a quantitative approach and the type of True-Experimental Design-posttest Only Control Design, in the sense that researchers can control all variables that influence the course of the experiment, through data collection techniques with observation, questionnaires, validity tests, and confidence tests. The results showed that through a program carried out at the Indonesia Stock Exchange Investment Gallery at STIE Nganjuk, it could increase students' independence in trading shares in the capital market.